2011
DOI: 10.3384/ecp110572198
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Power Conversion for Electricity Generation and Desalinated Water Production

Abstract: Ocean power is a promising source of renewable and alternative energy used to fuel human activities. Generated energy from ocean power devices can be converted into electrical or mechanical energy, which can in turn be used as a driving force together with the desalination and water treatment by reverse osmosis processes. In this article, applications of high pressure wave energy converters (WEC) and hydrokinetic turbine for current energy conversion (TEC), described in Estefen et al [1], are presented. Due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The MRE system may be customized to create a multi-output system, such as a wavedriven desalination system, that uses ORE resources to generate drinking water (W20 project, 2022), (WEC device using PTO system) (Nolan and Ringwood, 2006) and energy at the same time. Current research and development focus on systems combining ORE, power, and portable water production (Ferreira and Estefen, 2011;Leijon and Boström, 2018). Small islands and isolated places are typically not linked to the national grid and rely only on diesel generators for power.…”
Section: Economic and Socio-economic Benefits Of Mresmentioning
confidence: 99%
“…The MRE system may be customized to create a multi-output system, such as a wavedriven desalination system, that uses ORE resources to generate drinking water (W20 project, 2022), (WEC device using PTO system) (Nolan and Ringwood, 2006) and energy at the same time. Current research and development focus on systems combining ORE, power, and portable water production (Ferreira and Estefen, 2011;Leijon and Boström, 2018). Small islands and isolated places are typically not linked to the national grid and rely only on diesel generators for power.…”
Section: Economic and Socio-economic Benefits Of Mresmentioning
confidence: 99%
“…In order to effectively harness oceanic sustainable energy, such as wave energy, a comprehensive understand of the available resources and oceanographic circumstances in the target area is necessary [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several kinds of ocean power converter prototypes have been developed, according to the expertise of each inventing team and or specific issues from the local sea where it was designated [9][10][11][12][13][14]. These large numbers of prototypes and concepts indicated that the most suitable technology has not been defined to be applied for commercial purposes [9].…”
Section: Introductionmentioning
confidence: 99%